Dick and Jane. Go, go, go (Puffin Young Readers New York, 2012)
Dick, Jane, Sally, Tim, and even Spot find ways to go, go, go in this fun easy-to-read book. They ride bikes, wear roller skates, sail boats, and even travel in a wagon